Nolana balsamiflua (Gaudich.) Mesa (Solanaceae), un arbusto vulnerable del desierto de Atacama dependiente de polinizadores para producir semillas. - Humaña, Ana María; Jiménez , Alberto; Valdivia , Carlos E. (Gayana Botánica, 2020)
Pollinator-dependency for reproduction is of great importance for plants. We evaluated the breeding system of Nolana balsamiflua, a threatened endemic shrub of the Atacama Desert, performing four pollination trials. No flower produced seeds by agamospermy, autogamy and geitonogamy. However, xenogamy accounted for 51.4% of fruiting, indicating its full dependency on exogenous pollen and pollinators for reproduction.